Localization of the Domains of the Haemophilus ducreyi Trimeric Autotransporter DsrA Involved in Serum Resistance and Binding to the Extracellular Matrix Proteins Fibronectin and Vitronectin - Leduc, Isabelle (American Society for Microbiology (ASM), 2009)
Resisting the bactericidal activity of naturally occurring antibodies and complement of normal human serum is an important element in the evasion of innate immunity by bacteria. In the gram-negative mucosal pathogen Haemophilus ducreyi, serum resistance is mediated primarily by the trimeric autotransporter DsrA. DsrA also functions as an adhesin for the extracellular matrix proteins fibronectin and vitronectin and mediates attachment of H. ducreyi to keratinocytes. We sought to determine the domain(s) of the 236-residue DsrA protein required for serum resistance and extracellular matrix protein binding. A 140-amino-acid truncated protein containing only the C-terminal portion of the passenger domain and the entire translocator domain of DsrA exhibited binding to fibronectin and vitronectin and conferred serum resistance to an H. ducreyi serum-sensitive strain. A shorter DsrA construct consisting of only 128 amino acids was unable to bind to extracellular matrix proteins but was serum resistant. We concluded that neither fibronectin binding nor vitronectin binding is required for high-level serum resistance in H. ducreyi.